Exploratory Study of Xanthine Dehydrogenase (XD) Accumulation in Chicks’ Organs: XD Natures and its Inhibitory Activities - Aljerf, Loai; Al Hamwi, Bayan (JOURNAL OF ADVANCES IN BIOLOGY, 2018)
Few researches have indicated the availability of xanthine dehydrogenase in some parts of chicks, the enzymatic activity, and the rate of enzyme synthesis during the first few days after hatching. In addition, studies were conducted to examine the relationship between changes in xanthine dehydrogenase in some of these parts and some biomarkers as the excretion of uric acid in chicks fed diets. The developmental changes between xanthine oxidase in these parts and adenosine have also been observed before. However, in the current project, the developmental changes (including organ activity) in xanthine dehydrogenase activity of kidney, liver, pancreas and duodenum are investigated. Unincubated White Leghorn eggs and day-old male chicks were brought. Chicks were fed (Startena) ad libitum and eggs were injected in three sequential days and embryos were gotten on day 19th. Some organs (as liver, kidney, duodenum, and pancreas) tissues of the embryos were isolated and treated with potassium phosphate solution and treated with charcoal and centrifuged. The extracts were let to react with 2-amino-4-hydroxypteridine and NAD in phosphate buffer in order to check the activity using a fluorometer. Specific activities of the xanthine dehydrogenase in organ tissues are listed as micromicromoles of substrate oxidized per minute per milligram protein. Besides, the xanthine dehydrogenase activities in these active tissues were measured from day 17 of incubation to a week after hatching. We reached to a conclusion that the enzyme was formed in the kidney several days prior to hatching and this had stimulated the liver, duodenum, and kidney at hatching in addition, to the central nervous system which resulted in a sensible modification of the pituitary function. Tracking the xanthine dehydrogenase activities in these organs showed no influence on the enzymatic activities except for pancreas which related to dietary situation that clearly refers to a possible interfering agent in the food which opens new arguments. As a result, our study has lucratively discovered 3-types of xanthine dehydrogenases in fledglings.